Amphibia, Anura, Microhylidae, Gastrophryninae, Elachistocleis Bicolor Gurin Mneville, 1838: Distribution Extension and Geographic Distribution Map (Global Journal of Medical Research, 2013)
The geographic distribution of Elachistocleis bicolor (Anura: Microhylidae) extends over several biomes in Argentina, Bolivia, Paraguay, Peru, Uruguay and Brazil. In Brazil, this species was reported to occur in the States of Amazonas, Distrito Federal, Goiás, Mato Grosso do Sul, Paraná, Rio Grande do Sul, Santa Catarina and São Paulo. The current study reports the first record of E. bicolor for the state of Rondônia, Brazil, extending its distribution in 350 km eastwards from closest records in Beni, Bolivia and 715 km southwestwards from closest records in Amazonas.